Management of Delayed Priapism - Sarker, Ashok Kumar; Zim, Hasnat Zaman (Journal of Surgical Sciences, 2020)
Priapism is a disorder of persistent penile erection unrelated to sexual interest or desire. This pathologic condition, specifically the ischemic variant, is often associated with devastating complications, notably erectile dysfunction. This case is about a 35 year old gentleman who presented with four day old priapism. He was tried with irrigation and aspiration in another hospital with unsatisfactory resolution of the condition. Following admission duplex study was done which confirmed low flow priapism. After thorough evaluation glanulocavernous shunt shunt was done and detumescence of the penis was established within first 24 hour. Journal of Surgical Sciences (2019) Vol. 23(2): 100-103